Extended Chalcones: Synthesis, In Vitro Analysis, and In Vivo Testing Against a Drosophila melanogaster Alzheimer’s Disease Model - Aadya Jaipuria; Madison Castillo; James Boksanski; Greg Landry; Ji Hyung Beak; Michelle Young; David T. Priefer; Kaïs Guessab; Crystal N. Ellis; Ronny Priefer (Chemistry)
Alzheimer’s Disease (AD) is the most common form of dementia in individuals over the age of 65. There is no known prevention for the progression of the disease, although the FDA recently approved two drugs for AD. The exact etiology of AD is still under debate; however, it is commonly associated with the aggregation of amyloid-beta (Aβ) plaques in the brain. Recently some extended chalcones were reported to be potential anti-amyloidogenic agents. In this study, a larger library of extended chalcone analogs were synthesized with modifications on both rings. These were tested using the Thioflavin T fluorescence assay to measure their anti-Aβ aggregation properties. Three notably active compounds were further evaluated for potential neurotoxicity and neuroprotection using an MTT cell viability assay. These compounds were non-neurotoxic and displayed a trend toward neuroprotection. These were further assessed in a Drosophila melanogaster animal AD model. A forced climbing assay revealed statistically significant changes in flies’ movement by ~30% when fed these anti-amyloidogenic agents.